Antifungal activity of Eurycoma longifolia jack (Tongkat Ali) root extract - Faisal, Ghasak Ghazi; Zakaria, Siti Mastura; Najmuldeen, Ghazi Faisal; Al-Ani, Imad Matloub Dally (Ectodermal Dysplasia Group-Turkey, 2016)
Eurycoma longifolia jack (Tongkat Ali) has been known to possess many important biological properties and its uses are gradually expanding . To test the presence of antifungal activity of the ethanolic Eurycoma longifolia Jack (E.L) root extract. E.L. roots were extracted using ethanol . Two types of fungal strains were used; Candida albicans and Aspergillus fumigatus. Disc diffusion assay and Minimum inhibitory concentration (MIC) tests were used to determine the antifungal activity. The extract was prepared into three concentrations of 50, 100 and 150 mg/ml, Nystatin was used as positive control. The ethanolic extract of E. longifolia Jack root showed positive antifungal activity against C.albicans and A.fumigatus. The antifungal activity, measured through the zone of growth inhibition on the agar disc diffusion assay, against A.fumigatus was recorded to be 3.78±0.63, 6.11±1.45, 9.89±0.74mm, while for C.albicans was 4.44±0.5, 6.56±0.50, 8.44±0.90 mm for the extract concentrations of 50, 100 and 150 mg/ml respectively. The results of MIC showed the inhibition of visible growth of A.fumigatus and C.albicans at the minimum concentration of 12.5 and 25 mg/ml respectively. E.L root extract possesses potent antifungal properties and has the potential to be used as a medicinal product.